2017
DOI: 10.3390/su9081367
|View full text |Cite
|
Sign up to set email alerts
|

Elaborating the Role of Backbone Leadership Organizations in Sustainable Tourism Development: The Monongahela River Valley Coalition

Abstract: Leadership has emerged as a central factor in sustainable regional development. Complex regional development initiatives need dynamic leaders to convene diverse stakeholders, sustain participation, leverage external resources, and achieve collective impact. This study researched the deeper meanings and application of backbone leadership using case study research examining a collaborative, regional initiative known as the Mon River Valley Coalition (MRVC). The MRVC is a regional and community-based economic rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Sustainable tourism cannot be achieved until community members actively support tourism development [50,51]. Governments and markets require community support and participation in order to implement strategies for STD [35,52].…”
Section: Hypothesis 3 (H3)mentioning
confidence: 99%
“…Sustainable tourism cannot be achieved until community members actively support tourism development [50,51]. Governments and markets require community support and participation in order to implement strategies for STD [35,52].…”
Section: Hypothesis 3 (H3)mentioning
confidence: 99%
“…This highlights the need for more research on the impact of stakeholder configurations on collaborative governance, which is particularly relevant because previous collaborative governance contributions have not addressed the context of community-oriented destinations with established management bodies such as destination management organizations (DMOs) ( Table 1). Selin [17] highlighted the importance of leadership for collaborative approaches and also used the model by Ansell and Gash [19]. Drawing on the concept of backbone organizations [44], it was found that backbone leadership adds to the success of coalitions [17].…”
Section: Collaborative Governance In Tourismmentioning
confidence: 99%
“…Selin [17] highlighted the importance of leadership for collaborative approaches and also used the model by Ansell and Gash [19]. Drawing on the concept of backbone organizations [44], it was found that backbone leadership adds to the success of coalitions [17]. It appears promising to explore varying leadership roles in established, community-oriented destinations in order to show the varying roles of different stakeholders.…”
Section: Collaborative Governance In Tourismmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that some tourism entrepreneurs come from outsiders is advantageous because they provide new knowledge, perspectives and awareness of new possibilities, and therefore, are a source of creativity. The team members have to fill voids in key functions with complementary knowledge of the tourism sector, as well as being capable of building, maintaining and exploiting effective intra-and cross-organizational networks [98] as well as intra-and extra-traditional and political boundaries [98,99].…”
Section: Entrepreneurial Discoverymentioning
confidence: 99%